The Difference in the Influence of Source Credibility Nano and Micro Beauty Influencers on Parasocial Interaction and Purchase Intention of Instagram Users in Indonesia - Shafira Amalia; Ni Putu Nanda Pramesti Nata Putri; Nurfathiyah Mualifah Qalbi; Faranita Mustikasari (Green Publisher Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia often face limited marketing budgets, making cost-effective strategies crucial. One emerging approach is leveraging nano and micro influencers, who maintain closer engagement with audiences than larger-scale influencers. This study analyzes the impact of influencer credibility—attractiveness, trustworthiness, and expertise—on parasocial interaction (PSI) and purchase intention (PI), and compares differences between nano and micro influencers. Using a quantitative design, data were collected from 170 respondents through an online survey targeting skincare industry followers. Analysis employed Partial Least Square–Structural Equation Modeling (PLS-SEM) and Multi Group Analysis (MGA). Results confirm that influencer credibility positively and significantly affects both PSI and PI (H1–H6 accepted), while PSI also significantly influences PI (H7 accepted). Comparative analysis shows no significant differences across most hypotheses (H8–H14 rejected), except H13, which reveals that nano influencers’ expertise exerts a stronger impact on PI. These findings demonstrate that influencer credibility directly drives PSI and PI, with PSI reinforcing PI. Practically, the study highlights the value of both nano and micro influencers as viable digital marketing strategies for MSMEs, with nano influencers’ expertise offering a distinct advantage in boosting purchase intention.